Development of Natural Science E-Module on Motion Materials for Junior High School Students - Lazaro Kumala Dewi; Indri Astuti; Aloysius Mering (STKIP Singkawang, 2023)
The goals of this research are to produce an innovative, interactive, and practical Natural Science E-Module of Motion Materials, this learning can be more interesting, fun, and also the students can learn independently. This research using 4-D model (Four D-Models) with 4 steps they are define, design, develop, and disseminate/deploy. The subjects of this research were students of class VIII grade of SMP Negeri 1 Sungai Raya Pontianak and SMP Negeri 11 Pontianak. The data collecting of this research is using interview techniques, questionnaires, and tests. The assessment of E-Module by the experts obtained eligibility = 86,67% with